Estimating the oscillation frequency of a payload mass on quadcopter in non-autonomous flight - Geronel, Renan S [UNESP]; Dowell, Earl H; Bueno, Douglas D [UNESP] (My University, 2021)
Unmanned aerial vehicles (UAVs) have been employed in several engineering applications, such as aerial photography, environmental surveillance, delivery tasks, and others. Most of these applications have attracted increasing attention due to their ability to carry different payloads, which can change the dynamic of flight. The present article investigates the dynamics of a quadcopter with a payload mass including the stiffness of the attachment to the aerial vehicle. An approach to obtain non-dimensional equations of motion is introduced, and as a consequence, it is possible to determine the frequency of vibration of the payload mass during the flight. The results are presented for non-autonomous flight, and they establish a simple equation to estimate the oscillation frequency depending on the relation between the quadcopter and the payload masses, also considering the stiffness of attachment, without requiring a solution to the equation of motion in the time domain.
Keywords: non-autonomous flight; non-dimensional equation; oscillation frequency; payload; Unmanned aerial vehicles